Top honours - The, Star (The Star, 2011)
Sultan of Kedah Tuanku Abdul Halim Mu’adzam Shah conferring the Orang Besar Lapan, which carries the title Dato Seri Mahawangsa on former Kedah Mentri Besar Datuk Seri Diraja Mahdzir Khalid during the Kedah ruler’s 83rd birthday, which was held at Balai Penghadapan, Istana Anak Bukit, Alor Setar, Kedah, yesterday.